Effect of Doping Concentration on the Optical Properties of Indium-Doped Gallium Arsenide Thin FILMS (Journal of Bangladesh Academy of Sciences, 2016)
Effects of indium doping (concentration 0.2, 0.3 and 0.4%) on the optical properties of GaAs thin films were studied. Thin films of 600 nm were grown onto chemically and ultrasonically cleaned glass substrate by thermal evaporation method in high vacuum (~10-4 Pa) at 50°C fixed substrate temperature. The samples were annealed for 15 minutes at a fixed temperature of 200°C. The thicknesses of films were being measured in situ by a quartz crystal thickness monitor during deposition. The transmittance and reflectance data were found using UV-VIS-NIR spectrophotometer in the photon wavelength range of 310 ~ 2500 nm. These data were utilized to compute the absorption coefficient, refractive index, extinction co-efficient and band gap energy of the studied films. Here transmittance was found 78 for 0.2% indium doping concentration. The band gap energy decreased with the increase of doping concentration.Journal of Bangladesh Academy of Sciences, Vol. 40, No. 2, 179-186, 2016